2007
DOI: 10.1086/519159
|View full text |Cite
|
Sign up to set email alerts
|

Probing Inward Motions in Starless Cores Using the HCN(J= 1–0) Hyperfine Transitions: A Pointing Survey toward Central Regions

Abstract: We have carried out a survey toward the central regions of 85 starless cores in HCN(J ¼ 1 0) to study inward motions in the cores. Sixty-four cores were detected with HCN lines. The infall asymmetry in the HCN spectra is found to be more prevalent, and more prominent than in any other previously used infall tracers such as CS(J ¼ 2 1), DCO þ (J ¼ 2 1), and N 2 H þ (J ¼ 1 0). We have found a close relation between the intensities of the HCN and N 2 H þ lines. This implies that the HCN is not very depleted in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
80
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 30 publications
(32 reference statements)
7
80
0
2
Order By: Relevance
“…The distances to each core as listed in Table 1 were used to convert the radial offsets from the dust continuum peak for each pointing into a physical distance in parsecs. (Crapsi et al 2005) b (Schnee et al 2013) c (Kauffmann et al 2008) d (Di Francesco et al 2008) e Although Schnee et al (2013) labeled L492 as a "static core" due to the subtlety of its infall asymmetry in HCO + (3-2), this core has been classified as a "contracting core" by Sohn et al (2007) due to infall asymmetries in all three hyperfine components of HCN(1-0). Lee & Myers (2011) also classify L492 as a "contracting core" based on infall asymmetries determined from CS, HCN, and N 2 H + spectra.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distances to each core as listed in Table 1 were used to convert the radial offsets from the dust continuum peak for each pointing into a physical distance in parsecs. (Crapsi et al 2005) b (Schnee et al 2013) c (Kauffmann et al 2008) d (Di Francesco et al 2008) e Although Schnee et al (2013) labeled L492 as a "static core" due to the subtlety of its infall asymmetry in HCO + (3-2), this core has been classified as a "contracting core" by Sohn et al (2007) due to infall asymmetries in all three hyperfine components of HCN(1-0). Lee & Myers (2011) also classify L492 as a "contracting core" based on infall asymmetries determined from CS, HCN, and N 2 H + spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Although L1521F was originally thought to be prestellar, it has recently been found to be protostellar with a confirmed bipolar outflow originating from an embedded VeLLO (Bourke et al 2006;Takahashi et al 2013). All three cores have been found to have signatures of infall asymmetry in previous surveys (e.g., Crapsi et al 2005;Sohn et al 2007;Lee & Myers 2011;Schnee et al 2013). High-resolution spectral line emission maps have also been observed toward L694-2 (Williams et al 2006) which have shown a radial gradient of infall speeds across the core with decreasing speeds as distance from the center increases.…”
Section: Observationsmentioning
confidence: 92%
See 1 more Smart Citation
“…흥미롭게도 이 천체에 대한 CS 분자선 지도관측 결과는 중심으 로 향하는 수축운동을 지시하는 분광양상과 중심에서 밖으로 향하는 팽창 운동을 지시하는 분광양상이 공 존하여 나타났다 (Lee et al, 2001). 또한, CS 분자선 보다 고밀도 영역을 지시하고 화학적 모형계산 Aikawa et al, 2005)으로 밀도가 높은 영역에서 분자의 먼지포피 또는 얼음에 흡착되어 분 자선 관측 결과에서 그 밝기가 결핍 되어 나타나는 현상이 CS 분자선에 비하여 크지 않은 것으로 알려 진 HCN(J=1-0) 분자선을 통한 중심 관측 결과에서 도 HCN(J=1-0)의 3개 미세 천이선에서 서로 다른 방향성의 복잡한 운동양상이 보고되었다 (Sohn et al, 2007).…”
unclassified
“…Spitzer의 영상검출기에서 보여진 고깔모양의 성운상 모습이 중심 극저광도천체 에 의한 질량분출의 간접적인 증거로 제시되었다 (Bourke et al, 2006;Terebey et al, 2009 (Dalgarno and Lepp, 1984;Millar et al, 1989;Oliveira et al, 2003;Crapsi et al, 2005). 그 러나 이 천체는 CS 지도 관측에 의하면 중심을 기준 으로 대칭적인 상이한 운동 방향성을 보이고 HCN 중심 점 관측에서는 분광 천이 지시선에 따라 서로 상이한 운동 방향성을 시사하는 비대칭 분광선 윤곽 이 확인되었다 (Sohn et al, 2007;Lee et al, 2004). Table 1.…”
unclassified